Characterization and functional analysis of toll-like receptor 4 in Chinese soft-shelled turtle Pelodiscus sinensis. (October 2016) - Zhou, Yingshan; Liang, Quan; Li, Weifen; Gu, Yuanxing; Liao, Xun; Fang, Weihuan; Li, Xiaoliang
Abstract: Mammalian Toll-like receptor 4 (TLR4) recognizes lipopolysaccharide (LPS) in initiating the innate immune responses. Early studies indicate that turtles are more resistant to LPS challenge than mammals. It remains unknown if turtles express TLR4 and why they are more resistant to LPS. In this study, TLR4 gene from Chinese soft-shelled turtle, Pelodiscus sinensis, was cloned and characterized. The full length cDNA of turtle TLR4 (tTLR4) consists of 3396 base pairs with an 2499-bp open reading frame, encoding 833 amino acids. Phylogenetic and syntenic analyses suggest that tTLR4 is to be orthologous to human TLR4. Its mRNA expression was up-regulated in spleen and blood of turtles upon Aeromonas hydrophila infection. Stimulation of turtle peripheral blood monocytes with LPS significantly upregulated tTLR4 mRNA and inflammation-related gene expression, such as Interleukin-1β (IL-1β) and cyclooxygenase-2 (COX-2). In tTLR4-expressing HEK293 cells, higher concentration of LPS exposure could enhance the activity of the NF-κB promoter, but not the INF-β promoter. Such activity required co-expression of turtle myeloid differentiation factor 2 (tMD2) and cluster of differentiation 14 (tCD14). These results provide evidence for a functional TLR4 in reptiles and, together with the syntenic analysis, support the idea that the TLR4 receptor for LPS recognition may have arisen after reptiles. Highlights: First identification and partial characterization of turtle TLR4. Turtle TLR4 is responsive to microbial infection and LPS stimulation. LPS signaled via a TLR4-dependent manner in turtle. Fully functional TLR4 receptor for LPS recognition may have arisen after reptiles.